Characterization of the novel HLA‐A*80:04 allele identified in a Spanish volunteer donor. (4th September 2018) - Santos, Silvia; Rodriguez, Clara; Eguizabal, Cristina; Balas, Antonio; Vicario, José L.
Abstract : HLA‐A*80:04 shows one amino acid replacement, A76 > E, when compared with the A*80:01 allele.